Implementation Of The Concept Of Sustainable Development In Resolving Indigenous Law Community Conflict - Tumpal SIMANJUNTAK; Ratih LESTARINI (Indonesia Strategic Sustainability, 2022)
The purpose of this study is to explain the concept of sustainable development that needs to be implemented in resolving conflicts between indigenous peoples and how the government is making concrete efforts to realize the concept of sustainable development. This study uses a socio-legal approach because it uses non-legal elements in its study. The results of the study show that the values ??contained in the concept of sustainable development can be a means of resolving land conflicts of customary law communities. Considering the concept of sustainable development is also in line with the concept of Planning for Sustainable Use of Land Resources. The implementation of the concept of sustainable development in solving problems of conflict resolution of customary law communities is carried out through achieving goals with political will, consistent government customary law and companies, responsiveness of stakeholders including local governments to land conflicts, and the establishment of a sustainable maintenance system.